2016
DOI: 10.1097/ico.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thyroxine in the Development of Keratoconus

Abstract: Our data implicate a crucial role of T4 in KC pathophysiology, which is most likely mediated by T4Rs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 21 publications
0
32
0
6
Order By: Relevance
“…Moreover, the tear thyroxine levels of patients with keratoconus were found to be 2 to 50 times higher than those of patients without ocular diseases and levels were higher during the progression of keratoconus and declined once cornea curvature fulfilled a new steady value. Furthermore, a study by Thanos et al 17 showed that thyroid gland dysfunction prevalence among patients with keratoconus was 13.6%. Additionally, other studies by Tabibian et al 18 and Gatzioufas and Thanos 19 support our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the tear thyroxine levels of patients with keratoconus were found to be 2 to 50 times higher than those of patients without ocular diseases and levels were higher during the progression of keratoconus and declined once cornea curvature fulfilled a new steady value. Furthermore, a study by Thanos et al 17 showed that thyroid gland dysfunction prevalence among patients with keratoconus was 13.6%. Additionally, other studies by Tabibian et al 18 and Gatzioufas and Thanos 19 support our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Seven hundred and twelve eyes from the database of our HKC were included in this study. The aims of the HKC include research in diagnostics, longitudinal course of keratoconus, therapy options and influencing factors, such as the effect of thyroid gland function on keratoconus (Gatzioufas & Thanos 2008;Gatzioufas et al 2014;Thanos et al 2016) and have been described in detail previously (Goebels et al 2013(Goebels et al , 2015. In the HKC, patients from the outpatient service with unilateral or bilateral keratoconus were included, as well as patients with possible corneal abnormality and patients without noticeable ocular abnormality but with thyroid diseases.…”
Section: Patientsmentioning
confidence: 99%
“…Thanos and co-authors also found higher levels of tear thyroxine in KCs, as well as high expression of thyroxine receptors in the KC stromal cells, when compared to healthy controls [2]. While very limited literature exists on thyroxine and KC, it is known to play a role in metabolism and physiological function of the cornea as well as other tissues [2]. Furthermore, in a recent case study, published by Lee et al [38], a 17-year-old girl underwent partial thyroidectomy without thyroid hormone replacement therapy with a normal baseline ophthalmic exam.…”
Section: Discussionmentioning
confidence: 86%
“…Thyroxine levels in blood (serum) of these patients, however, showed no significant changes. Thanos and co-authors also found higher levels of tear thyroxine in KCs, as well as high expression of thyroxine receptors in the KC stromal cells, when compared to healthy controls [2]. While very limited literature exists on thyroxine and KC, it is known to play a role in metabolism and physiological function of the cornea as well as other tissues [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation